Applications and Challenges of Artificial Intelligence in the Field of Cybersecurity - Yang, Qiyue (Transactions on Computer Science and Intelligent Systems Research, 2025)
With the rapid development and widespread application of computer technologies, cyber-attacks have become increasingly diverse and intelligent. Traditional cyber defense methods are no longer sufficient to meet current security demands. Therefore, introducing more efficient and intelligent protection technologies has become critically important. This paper focuses on the applications and challenges of artificial intelligence (AI) in the field of cybersecurity. Through a combination of literature review and case analysis, it systematically examines the application of AI in areas such as intrusion detection, malware identification, vulnerability discovery and risk assessment, threat intelligence analysis, and data center security. Furthermore, it evaluates the challenges AI faces in terms of interpretability, data quality, implementation costs, interdisciplinary collaboration, privacy protection, and system vulnerabilities. The findings indicate that AI technologies are widely adopted in the cybersecurity domain, significantly advancing the development of security techniques. Looking ahead, further efforts in technology, systems, talent development, and policy coordination are required to build intelligent security frameworks and to promote the deeper integration of AI in cybersecurity.